2016
DOI: 10.1136/annrheumdis-2015-208387
|View full text |Cite
|
Sign up to set email alerts
|

Examination of overall treatment effect and the proportion attributable to contextual effect in osteoarthritis: meta-analysis of randomised controlled trials

Abstract: ObjectiveTo examine the overall treatment effect and the proportion attributable to contextual effect (PCE) in randomised controlled trials (RCTs) of diverse treatments for osteoarthritis (OA).MethodsWe searched Medline, Embase, Central, Science Citation Index, AMED and CINAHL through October 2014, supplemented with manual search of reference lists, published meta-analyses and systematic reviews. Included were RCTs in OA comparing placebo with representative complementary, pharmacological, non-pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 27 publications
5
161
3
6
Order By: Relevance
“…Indeed, a recent meta-analysis found that nonspecific and contextual effects were responsible for 75% of treatment effects in clinical trials in patients with osteoarthritis. 70 To minimize recall bias, subjects received daily text message reminders to record amount of home practice. We doubt that these messages affected adherence to the home practice, because most subjects (80%) reported at least one full week without any home practice, despite having received the daily text reminders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis found that nonspecific and contextual effects were responsible for 75% of treatment effects in clinical trials in patients with osteoarthritis. 70 To minimize recall bias, subjects received daily text message reminders to record amount of home practice. We doubt that these messages affected adherence to the home practice, because most subjects (80%) reported at least one full week without any home practice, despite having received the daily text reminders.…”
Section: Discussionmentioning
confidence: 99%
“…Although placebo effects are greater after invasive interventions such as surgery,31 32 they are also present from non-invasive passive treatments such as inactive ultrasonography and inert gel 33. In exercise studies, where the patient, not the therapist, performs the intervention, placebo effects are less obvious, although attention effects cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…An effect size of 0.5, or thereabouts, is of considerable clinical value, and comparable to that of many of our commonly used interventions [16]. The same group published a further analysis, in which they used random-effects modelling to calculate the amount of pain relief that could be attributed to placebo (contextual) effects, and how much to the treatment being tested for its effects on pain in OA [17]. They report that on average 75% of the overall treatment effect is due to the contextual factors rather than the specific intervention.…”
Section: The Efficacy and Effectiveness Of Placebo On Pain In Oamentioning
confidence: 98%